Lectotypification of 13 names in Apiaceae, Malvaceae, and Rosaceae based on material housed at the herbaria NAS and NF - Li, Meng; Li, Yong-Fu; Duan, Yi-Fan; Zheng, Sun-Yuan; Li, Wei-Hong; Zhang, Cheng; Ma, Tu; Wang, Xian-Rong (Phytotaxa, 2017)
Thirteen names in three families based on material at the herbaria NAS and NF are lectotypified. These names include: Acronema chienii Shan & Liou, A. chienii Shan & Liou var. dissectum Shan & Liou, Angelica omeiensis Yuan & Shan, A. tianmuensis Pan & Zhuang, Arcuatopterus filipedicellus Sheh & Shan, A. linearifolius Sheh & Shan, A. thalictrioideus Sheh & Shan, Ostericum maximowiczii Kitagawa var. alpinum Yuan & Shan, Peucedanum rubricaule Shan & Sheh, P. wulongense Shan & Sheh, Photinia dabeishanensis Deng & Yao, Pternopetalum caespitosum Shan, and Tilia hupehensis Cheng ex H.T.Chang.